2005
DOI: 10.1086/502510
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine: Immunization Rates, Knowledge, and Attitudes of Resident Physicians in an Urban Teaching Hospital

Abstract: RPs have low immunization rates and significant gaps in knowledge regarding influenza immunization. These problems should be addressed during their training by education on the importance, effectiveness, and safety of influenza vaccine for them and their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Just as previous studies reported that 27% to 45% of HCWs think that the influenza vaccine could cause influenza infection [4,39], 38.1% of all respondents in our study shared this misconception.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Just as previous studies reported that 27% to 45% of HCWs think that the influenza vaccine could cause influenza infection [4,39], 38.1% of all respondents in our study shared this misconception.…”
Section: Discussionsupporting
confidence: 59%
“…Its short incubation period and efficient transmission from person to person makes influenza hazardous to the patients and staff in health care facilities [4]. Rates of serious illness and death are highest among persons over 65 years of age [5,6], children aged younger than two years [7], and persons of any age who have medical conditions that place them at increased risk for complications from influenza [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recommendations, only 36% of HCWs in the United States are vaccinated against influenza annually 8 . Other previous studies demonstrate a range of immunization rates for overseas doctors from 38% to 82% 9 , 10 …”
Section: Introductionmentioning
confidence: 81%
“…A study performed in the US found that only 38.3% of primary care physicians were immunized in 2003-2004, a value that is similar to the 37.6% reported for residents. 19 In both groups, the main reason for declining influenza vaccination was that the procedure was a waste of time, which only underlines how unimportant HCWs consider the disease and its prevention. 19 Furthermore, various data clearly show that the limited use of influenza vaccine by HCWs is strictly related to a lack of information about the recommendations concerning influenza vaccine use.…”
Section: Main Reasons For Poor Compliance With Recommendationsmentioning
confidence: 99%
“…19 In both groups, the main reason for declining influenza vaccination was that the procedure was a waste of time, which only underlines how unimportant HCWs consider the disease and its prevention. 19 Furthermore, various data clearly show that the limited use of influenza vaccine by HCWs is strictly related to a lack of information about the recommendations concerning influenza vaccine use. [20][21][22][23][24][25][26] One good example of the attitude of HCWs toward influenza vaccination is provided by the first data collected in Italy in a Department of Maternal and Pediatric Sciences 27 and in one of the largest Italian University Hospitals.…”
Section: Main Reasons For Poor Compliance With Recommendationsmentioning
confidence: 99%